Analisis Penerapan Prosedur Audit Akun Kas pada Organisasi Nirlaba Yayasan Pendidikan oleh KAP Djoko Soerjadi - Muhammad Syaiful Anwar; Wijaya, R. Muh Syah Arief Atmaja (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the implementation of audit procedures on the cash account in nonprofit organizations, specifically in the P Educational Foundation, conducted by the Public ccounting Firm Djoko Soerjadi. The research employs a qualitative approach with the P Educational Foundation as the object of study. Primary data were obtained through direct observation during the audit process. The resulty indicate that the applied audit procedures include the determination of materiality levels, preparation of audit working papers, reconciliation of cash balances between financial statements and the general ledger, examination of bank statements, and the sending of bank confirmation letters. All cash audit procedures were carried out systematically and in accordance with applicable auditing standars in Indoensia. Theses findings suggest that the audit procedures performed by the Public Accounting Firm Djoko Soerjadi were conducted professionally and contributed to ensuring the transparency and accountability of the P Educational Foundation’s financial statements.